Penerapan Metode Latihan Passing Aktif untuk Meningkatkan Keterampilan Passing Pemain Futsal SMP Negeri 14 Lubuklinggau - Sorita, Asri Putra; Supriyadi, Muhammad; Syafutra, Wawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the improvement of basic passing skills through active passing training methods on the basic passing skills of futsal players at SMP Negeri 14 Lubuklinggau. This research uses an experimental method with a